A casa-pátio como resposta arquitetónica para habitar no deserto costeiro. - Jéssica Andreia Correia Pinto (2019)
In order to design a pertinent housing complex in the coastal desert where the city of Arica is located, the need arises to question the dwell, in the search for this spirit to incorporate the climate and the surrounding in the architectural process of the vernacular or erudite dwellings. In this sense, the research intends to understand the answers and solutions of Arica, as well as other places with similar physical characteristics, returning to the beginning, to be able to start again and confer an identity to the architecture that seeks to draw, with the intention of responding with a more open attitude trying to do the things better, maintaining the strong sensitivity to the place, with the desire to be in harmony with it.